Principals’ human relation strategies and Teachers’ Job performance in Secondary Schools in Patigi Local Government Area of Kwara State - Awodiji, Omotayo Adewale; Etejere, Patricia A. O.; Oluwalola, Felicia K.; Eniola-arigbe, Yetunde; Fawale, Afiss Adebayo; Ololo, Kennedy Okechukwu (African Journal of Behavioural and Scale Development Research, 2019)
Building a strong culture of collaboration and creative problem-solving organisation demands instructional leadership qualities that possess appropriate human relations among all staff in a school for achieving effective teaching and learning. This study, therefore, investigated principals' human relation strategies and level of secondary schools teachers' job performance in Patigi Local Government Area of Kwara State. A descriptive design of a correctional type was adopted. Fifteen out of 20 schools in Patigi Local Government Area were randomly selected while one school principal, two Vice-principals, three HODs and six teachers were selected using stratified random sampling techniques from each sampled school totalling 180 respondents. Two validated questionnaires (PHRSAQ and TJPQ) with reliability coefficient of .87 and .68 were used to elicit information from the respondents. Descriptive statistic of mean rating and inferential statistic of Pearson product moment correlation were used for data analysis. The study revealed, among others, that there is a positive non-significant relationship between human relations strategies of principals and teachers' job performance in secondary schools (r = .12, p value .240 > .05). The study therefore recommended that training or capacity building programmes on human relations strategy should be organised for principals of secondary schools of the sampled area.